Riemann-Liouville fractional integro-differential equations with fractional nonlocal integral boundary conditions - Ahmad, Bashir; Nieto, Juan J (Boundary value problems, 2011)
This article investigates a boundary value problem of Riemann-Liouville fractional integro-differential equations with fractional nonlocal integral boundary conditions. Some new existence results are obtained by applying standard fixed point theorems. 2010 Mathematics Subject Classification : 26A33; 34A34; 34B15.